Scan QR code or get instant email to install app

Skip to content
#
Simplify the given expression. \((4-2)^2-(7-2)^3\) =

### Related Information

Question:

`_________`

.
A
\(-121\)

explanation

Following the rules of order of operations, we must first simplify the expressions inside the parentheses.

Then we can apply the exponents and after that, subtract.

\((4-2)^2-(7-2)^3\)

\(= 2^2-5^3\)

\(= 4 − 125 = −121\)

Take more free practice tests for other GED topics with our ged online now!

Comments